POLITIK HUKUM PERLINDUNGAN BAHASA BANGGAI SEBAGAI WUJUD PEMENUHAN HAK ASASI MANUSIA - Halimah Usman Hamid (Universitas Tadulako, 2025)
Banggai language is experiencing the same degradation as the languages in Indonesia experiencing the process of extinction because the number of speakers, especially the younger generation, who began to rarely speak Banggai language became a serious threat to Banggai culture. Protection in the context of legal politics, namely legal instruments in the form of regional regulations, is important especially in the context of regional autonomy where regions are given the authority to regulate and preserve regional languages in the form of legal instruments based on Law of the Republic of Indonesia Number 5 of 2013 concerning the Establishment of Banggai Laut Regency in Central Sulawesi Province. This writing aims to determine the legal politics of the Banggai Language as a form of fulfillment of human rights. This writing uses empirical research that emphasizes data collection based on observation and concrete facts. The results showed that first, the legal politics of Banggai Language protection as a form of fulfillment of human rights aims to protect and guarantee the basic rights of using Banggai Language, increasing public legal awareness to respect Banggai Language so that degradation does not occur, avoiding Indonesian Language, regional languages, especially Banggai Language in each region experiencing degradation or extinction. Second, the Legal Politics of Regional Language Protection in the Preamble of the 1945 Constitution in the 4th paragraph, Article 42 of Law Number 24 of 2009, Article 32 of the 1945 Constitution Paragraph 2, Third, the Legal Politics of Banggai Language Protection is contained in Banggai Laut Regional Regulation No. 15 of 2021. Salah satu permasalahan pelik yang dihadapi oleh berbagai bangsa-bangsa di dunia akibat kemajuan peradaban dunia adalah kebudayaan yang meliputi; kearifan budaya local, adat-istiadat, serta bahasa. Bahasa Banggai yang mengalami degradasi sama dengan bahasa-bahasa daerah lainnya di Indonesia. Degradasi atau proses kepunahan disebabkan jumlah penutur terutama generasi muda yang mulai jarang menuturkan Bahasa Banggai sehingga menjadi ancaman serius terhadap kebudayaan Banggai. Perlindungan dalam konteks politik hukum yaitu perangkat hukum berupa perda menjadi penting apalagi dalam konteks Otonomi melahirkan kewenangan untuk mengatur dan melestarikan bahasa daerah dalam bentuk perangkat hukum berdasarkan Undang-Undang Republik Indonesia Nomor 5 Tahun 2013 Tentang Pembentukan Kabupaten Banggai Laut di Provinsi Sulawesi Tengah. Penulisan ini bertujuan untuk mengetahui politik hukum Bahasa Banggai sebagai wujud pemenuhan hak asasi manusia. Penulisan ini menggunakan penelitian empiris yang menekankan pada pengumpulan data berdasarkan, observasi dan fakta konkret di lapangan. Hasil penelitian menunjukkan bahwa; pertama, politik hukum perlindungan Bahasa Banggai sebagai wujud pemenuhan hak asasi manusia bertujuan untuk melindungi dan menjamin hak dasar penggunaan bahasa Banggai, meningkatnya kesadaran hukum masyarakat untuk menghargai bahasa Banggai agar tidak terjadi degradasi, terhindarnya Bahasa Indonesia, bahasa daerah khususnya bahasa Banggai di tiap-tiap daerah mengalami degradasi atau kepunahan. Kedua, Politik Hukum Perlindungan Bahasa Daerah dalam Pembukaan Undang Undang Dasar 1945 Alinea ke 4, Pasal 42 Undang Undang Nomor 24 Tahun 2009, Pasal 32 Undang Undang 1945 Ayat 2 , Ketiga Politik Hukum Perlindungan Bahasa Banggai tertuang dalam Peraturan Daerah Banggai Laut No 15 Tahun 2021